Analysis of the Effectiveness of Village Fund Allocation Management in Realizing Good Governance in Village Pahlawan Batubara District - Anggi Pratama Nst; Ikhah Malikhah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze, and assess how effective the management of village fund allocations is and to provide information about what factors can increase the effectiveness of village fund allocation management in realizing good governance in the Hero Village, Batubara Regency. The management of Village Fund Allocation is reviewed based on law number 6 of 2014. The research approach was developed using a qualitative descriptive method. This study uses primary data sources such as the Village Head, Village Secretary, and Village Treasurer and added several community leaders in the village environment. Then the data obtained and analyzed using descriptive research is done by comparison or connecting with other variables. Effectiveness of Village Fund Allocation Management which is reviewed based on law number 6 of 2014 At the Hero Village, Batubara Regency has been running Effectively because it has been able to reflect the Clarity of Goals to be achieved, Clarity of Strategy for Achievement of Goals, Process of Policy Analysis and Formulation, Appropriate Planning and Programming right. Furthermore, the Management of Village Fund Allocations in the Hero Village, Batubara Regency has been effective because it has implemented all indicators starting from Planning, Administration, Management, Reporting, and Accountability There are Factors that can Increase the Effectiveness of Village Fund Allocation Management in realizing good governance in the Hero Village Batubara Regency, namely the High Interest in Community Participation, Qualification of Village Apparatus Resources and Level of Understanding Related to Regulation and Management of Village Fund Allocation